Apakah Empati Mempengaruhi Kepatuhan Pajak? - Joko Sustiyo; Danang Desta Yudha (Politeknik Ganesha Medan, 2022)
Research on the impact of empathy as a non-economic factor on taxpayer compliance has not been studied in Indonesia. Most research still focuses on economic factors that affect tax compliance. To find out whether empathy affects tax compliance, this study uses binary logistic regression analysis because the dependent variable is nominal and categorical. The significance of the regression equation parameters was tested by the Ratio Likelihood Test and the Wald Test. Then, the goodness of fit model was tested using the Hosmer-Lemeshow Test. The likelihood ratio test shows that there is at least one coefficient from the regression model that has an effect on the 5% significance level. Based on the Wald test, there is no independent variable that has a significant effect on tax compliance with a 5% significance level. The Hosmer-Lemeshow test states that the binary logistic regression model in this study is feasible to use. Binary logistic regression analysis shows that only one predictor has a significant effect on the tax compliance variable, namely empathic concern items. The odds ratio value of 1.054 on the empathic concern items variable shows that taxpayers who have empathy will be 1.054 times more tax compliant than respondents who do not have empathy. In other words, respondents who have empathy will tend to be more obedient in paying taxes than those who do not have this trait. Therefore, the government can formulate regulations that support the emergence of empathic concern items in the community so that tax compliance increases.